2017
DOI: 10.3892/ol.2017.6556
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of phenylhexyl isothiocyanate and LY294002 on the PI3K/Akt signaling pathway in HL-60 cells

Abstract: Abstract. The aim of the present study was to investigate the synergistic effect of phenylhexyl isothiocyanate (PHI) and LY294002 [an inhibitor of phosphoinositide 3-kinase (PI3K)] on the PI3K/protein kinase B (Akt) signaling pathway, modulating histone acetylation, inhibiting cell viability and inducing apoptosis in HL-60 cells. The inhibition of HL-60 cell viability was monitored using an MTT assay. Cell apoptosis was measured using flow cytometry. Expression of acetylated histone H3 and histone H4, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Moreover, we found that the apoptosis rates of CCA stem cells treated with GATA1 silencing and PI3K/AKT pathway inactivation were significantly increased. A former research demonstrated the association of LY294002 with apoptosis of human nasopharyngeal carcinoma,37 and other studies also revealed that LY294002 is capable of inducing apoptosis in HL-60 cells38 and promoting cell apoptosis caused by melatonin 39. It was also reported that osthole promotes apoptosis while impeding proliferation through the PI3K/AKT pathway in intrahepatic CCA 24.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, we found that the apoptosis rates of CCA stem cells treated with GATA1 silencing and PI3K/AKT pathway inactivation were significantly increased. A former research demonstrated the association of LY294002 with apoptosis of human nasopharyngeal carcinoma,37 and other studies also revealed that LY294002 is capable of inducing apoptosis in HL-60 cells38 and promoting cell apoptosis caused by melatonin 39. It was also reported that osthole promotes apoptosis while impeding proliferation through the PI3K/AKT pathway in intrahepatic CCA 24.…”
Section: Discussionmentioning
confidence: 91%
“…AKT can also play a significant role in the differentiation of some Yang, Huang, Zou, and Ma (2017) Note. HAT: histone acetyltransferase; HSCs: hematopoietic stem cells.…”
Section: The Importance Of Akt and Its Role In Erythropoiesismentioning
confidence: 99%
“…Our data showed that leonurine exhibited significant inhibitory effects on the phosphorylation of PI3K and Akt in HL-60 and U-937 cells. Previous reports (Lu et al 2015;Yang et al 2017) have proven the relationship of the PI3K/ Akt pathway with apoptosis. The PI3K inhibitor LY294002 has been proven to inhibit HL-60 proliferation and induce cell apoptosis.…”
mentioning
confidence: 95%